UZBEKISTAN'S ACCESSION TO THE WORLD TRADE ORGANIZATION (WTO): CHALLENGES AND SOLUTIONS - Barnokhon Aliyeva Akhrorjon kizi (European Science Publishing, 2025)
This article analyzes Uzbekistan's process of joining the World Trade Organization (WTO). The main challenges and their solutions are examined within the framework of economic, legal, social, and political aspects. Additionally, the anticipated benefits and strategic importance of WTO membership for our country are discussed.
Keywords: Uzbekistan, World Trade Organization, economic reforms, legal reforms, international trade, investments, competitiveness.